Mal me quer, bem me quer: uma análise dos cuidados dispensados ao idoso asilar - Casadei, Marina Coimbra; Silva, Antonio Carlos Babosa da; Justo, José Sterza [UNESP] (My University, 2011)
This article aims to portray a survey in order to see whether the established in the Practical Guide Caregiver program (Ministry of Health, established in 2008 to improve the care for the elderly), are also affecting the nursing homes of smaller towns, with reference to a city in São Paulo State, with approximately 100,000 inhabitants located in western Sao Paulo State.

Este artigo retrata uma pesquisa realizada com o objetivo de observar se as condutas estabelecidas no Guia Prático do Cuidador (programa do Ministério da Saúde, implantado em 2008 para a melhoria do cuidado do idoso), estão sendo praticadas também em instituições asilares de cidades menores, tomando como referência uma cidade do interior paulista, com aproximadamente 100.000 habitantes, localizada no Oeste do Estado de São Paulo.
Well me either, me either ill: a review of care provided to elderly asylum
Keywords: Elderly; Caregiver; Practical Guide; Idosos; Cuidador; Guia prático